Prolonged visual perceptual changes induced by short-term dyadic training: The roles of confidence and autistic traits in social learning - Bin Zhan; Yujie Chen; Rui Wang; Yi Jiang (iScience)
Summary: As social creatures, we are naturally swayed by the opinions of others, which largely shape our attitudes and preferences. However, whether social influence can directly impact our visual perceptual experience remains debated. We designed a two-phase dyadic training paradigm where participants first made a visual categorization judgment and then were informed of an alleged social partner’s choice on the same stimulus. Results demonstrated that social influence significantly modified participants’ subsequent visual categorizations, even when they had been well-trained prior to the dyadic training. This effect persisted for an extended period of up to six weeks. Diffusion model analysis revealed that this effect stemmed from perceptual processing more than mere response bias, and its strength was inversely related to the participants’ confidence and autistic-like tendencies. These findings offer compelling evidence that our perceptual experiences are deeply influenced by social factors, with individual confidence and personality traits playing significant roles.